THE SYNTHESIS OF A NOVEL BIBENZOPYRAN RELIED ON ELECTROOXYDATION OF MALLOAPELTA B BY CYCLIC VOLTAMMETRY - Phan Thi Binh; Bui Hai Ninh; Chau Van Minh; Nguyen Hoai Nam; Le Mai Huong; Phan Van Kiem (Universitas Gadjah Mada, 2007)
A novel bibenzopyran named bimalloapelta (1) was synthesized relying on electrooxydation of malloapelta B by cyclic voltammetry in acetonitril adding LiClO4 0.1 M as supporting electrolyte. Its structure determination based on extensive NMR studies and ESI mass spectral measurements. The new compound showed significant cytotoxicity againsts two cancer cell lines as human hepatocellular carcinoma (Hep-2; IC50: 0.46 µg/m) and rhabdosarcoma (RD; IC50: 0.33 µg/m). These results were the same that of malloapelta B (Hep-2, IC50: 0.49 µg/ml and KB, IC50: 0.54 µg/ml).